Entrepreneurial Skills Improvement Through Creative Mocktail Training For Inmates At Barelang Prison - Sipayung, Natal Olotua; Dailami; Moh. Thandzir; Syafruddin Rais; Steven Johnson (JURNAL KEKER WISATA, 2025)
Entrepreneurship training really needs to be applied in everyday life. This training can not only be carried out to the general public but also inmates. One of the materials that can be provided to inmates is entrepreneurship training in making creative mocktails. In this training, inmates at Lapas Kelas II (Class II Prison) in Barelang Batam were given material in the form of knowledge about mocktails, the equipment needed to make mocktails and how to use them and also the method of making and practicing making mocktails directly. Through this training, it is hoped that the inmates of Class II Barelang Prison will have knowledge about mocktails and be able to make mocktails so that they can become an entrepreneurial option when they are released from detention.